IDENTIFIKASI KANDUNGAN (ANTIOKSIDAN, VITAMIN C DAN SERAT KASAR) PADA BUAH LOKAL DAN IMPOR (JERUK, APEL DAN MANGGA) - Asep Dedy Sutrisno (Pasundan Food Technology Journal (PFTJ), 2019)
The purpose of this study was to determine the contents (antioxidant, vitamin C, and crude fiber) contained in local and imported fruits which are the commodities of orange, apple, and mango. Benefits expected from this research are providing information to the society about the benefits of fruit contents (antioxidant, vitamin C, and crude fiber) in local and imported fruits (Orange, apple, and mango) and informing that there are differences in contents (antioxidant, vitamin C, and crude fiber) of the three commodities. The research used purposive sampling method which has been done by several step, they were Market Survey (supermarket/hypermarket) in Bandung City, Determination the number of samples, Sampling, Sample Preparation, and Sample testing. Responses in this research were chemical responses which include antioxidant activity by DPPH method, Vitamin C content by iodometric titration method, and crude fiber content by gravimetric method. The result of content identification (antioxidant, vitamin C, and crude fiber) on local and imported fruits (orange, apple, and mango) from supermarket / hypermarket in Bandung city found that the local fruits have different nutritional quality compared to the imported fruits. This is influenced by the longer time needed for distribution and storage on the imported fruits compared to the local fruits that tend to be faster in mobility.